Evaluating the surgical outcomes of distal radius fractures treated with locking plate fixation at Hue University of Medicine and Pharmacy Hospital - Tran, Nhat Tien; Le, Phuong Thao; Le, Hong Phuc (Tạp chí Y Dược Huế, 2026)
Background: Distal radius fractures are among the most common fractures, particularly in older adults following a fall onto an outstretched hand, and are associated with impaired wrist function and reduced quality of life. Open reduction and internal fixation using locking plates provides stable fixation, limits secondary displacement, and facilitates earlier functional recovery. Objective: To evaluate the surgical outcomes of distal radius fractures treated with locking plate fixation at Hue University of Medicine and Pharmacy Hospital. Materials and Methods: This prospective longitudinal study included 42 patients who underwent surgical fixation of distal radius fractures using locking plates at Hue University of Medicine and Pharmacy Hospital between March 2023 and June 2025. Results: Most patients were older than 60 years, and females accounted for 71.4% of the cohort. The predominant injury mechanism was low-energy domestic falls, with AO/OTA fracture types B3 and C2 being the most common. Radiographic parameters assessed using the Scheck criteria showed significant postoperative improvement. At 6 months, functional outcomes assessed by the Green and O’Brien score were rated as good or excellent in 97.6% of patients. According to the QuickDASH score, the majority of patients had returned to normal function at 6 months (88.1%). No major postoperative complications were recorded. However, neither upper extremity functional recovery (QuickDASH or Green & O’Brien scores) nor postoperative anatomical restoration on radiographs differed significantly among fracture types classified according to the AO system. Conclusion: Surgical treatment of distal radius fractures using locking plate fixation yields favorable functional outcomes with a low complication rate.